1980
DOI: 10.1029/ja085ia03p01297
|View full text |Cite
|
Sign up to set email alerts
|

On ‘potential’ well treatment for atmospheric gravity waves

Abstract: The problem of gravity wave propagation in the lower atmosphere may be formally reduced into a scattering problem with an effective 'potential.' In such a formalism, the eigenvalues (in units of inverse square horizontal phase velocity) may be discrete, corresponding to fully guided modes ('bound' states) and partially guided modes ('resonance' states), or they may be continuous, corresponding to free modes ('scattering' states). A phase shift analysis reveals two 'resonance' states corresponding to horizontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…The second school [Yu et al, 1980] considers the behavior of the reflection coefficient at the same upper boundary when a gravity wave from above the upper boundary is reflected by all the atmospheric structure as well as the rigid ground below the boundary. Unlike the first school, this method conserves flux, since only the rigid surface ground boundary condition is used and the vertical wave vector is hence allowed to remain real.…”
mentioning
confidence: 99%
“…The second school [Yu et al, 1980] considers the behavior of the reflection coefficient at the same upper boundary when a gravity wave from above the upper boundary is reflected by all the atmospheric structure as well as the rigid ground below the boundary. Unlike the first school, this method conserves flux, since only the rigid surface ground boundary condition is used and the vertical wave vector is hence allowed to remain real.…”
mentioning
confidence: 99%
“…Owing to the earth's ground surface which forms a definite lower boundary and an uneven atmospheric structure, gravity waves were also known to propagate in partially guided (leakage) and fully guided modes (see, for example, Yeh and Liu 1-1974-1, Hines 1-1974-1, and Francis 1-1975-1). Later on, it was found that uneven atmospheric dissipation can also produce partially guided modes and that, in particular, the well-known high-speed F region modes associated with the large-scale TID [Thome, 1968-1 are very likely caused by dissipation [Tuan, 1976;Richmond, 1978;Yu et al, 1980]. In the present paper we wish to show that these three types of gravity wave modes can 'interfere' among themselves.…”
mentioning
confidence: 80%
“…In this paper we wish to consider the effect of gravity waves on H and O3 as well as OH emissions using a gravity model [Tuan, 1976;Yu et al, 1980] which satisfies the rigid surface boundary condition at ground level and can provide for guided as well as free modes. The undisturbed hydrogen and ozone profiles are taken from Good [1976] and T. J. Keneshea and S. P. Zimmerman (private communication, 1979).…”
Section: Omentioning
confidence: 99%
“…The model we use [Tuan, 1976;Yu et al, 1980] Zimmerman (private communication, 1979). In Figures 3 and 4 we show the 'unperturbed' variations in the ozone and hydrogen number density as a function of altitude.…”
Section: Theoretical Formulationmentioning
confidence: 99%